Identification and functional analysis of two drosophila mothers against decapentaplegic protein(Smad)genes and their involvement in immune responses in the red swamp crayfish Procambarus clarkii. Issue 131 (December 2022) - Zhang, Yan-Mei; Lin, Chen-Yang; Li, Bang-Ze; Dong, Wei-Ren; Shu, Miao-An
Abstract: Drosophila mothers against decapentaplegic proteins (Smads), the crucial signal transducers in activating downstream gene transcription through transforming growth factor beta (TGF-β) receptors, are the pleiotropic factors with important role in mediating cell proliferation, homeostasis, differentiation, apoptosis and immune response. However, whether Smads are involved in immune response in crustaceans remains unexplored. In the present study, the Smad3 and Smad4 were firstly identified and functionally characterized from the Red Swamp Crayfish Procambarus clarkii . The full-length cDNAs of pc Smad3 and pc Smad4 were 1, 670 bp and 3, 060 bp with 1, 326 bp and 1, 875 bp open reading frame (ORF), respectively. Real-time PCR analysis of the expression profiles demonstrated that pc Smad3 and pc Smad4 were predominantly expressed at in stomach, heart, and hemocytes. Notably, the expression levels of pcSmad3 and pcSmad4 both Aeromonas hydrophila and WSSV challenges were significantly altered, suggesting the involvement of pc Smad3 and pc Smad4 in innate immune responses. Knockdown of pc Smad3 and pc Smad4 in vivo dramatically activated the transcriptions of NF-κB signaling genes and anti-lipopolysaccharide factor genes. The overexpression of pcSmad3 and pcSmad4 could significantly activate NF-κB signaling in HEK293T cells. Meanwhile, the clearance of bacteria was significantly reduced with knockdown of pc Smad3 and pc Smad4 in vivo. Results indicated that pc Smad3 and pc Smad4 played an immune-regulatory role in crayfish's innate immunity, which might pave the for a better understanding of the TGF-β superfamily members in crustacean. Highlights: Smad3 and Smad4 genes were firstly identified and characterized in crustacean species. Smad3 and Smad4 responded to both Aeromonas hydrophila and WSSV challenges. Smad3 and Smad4 contributed to innate immunity by regulating NF-κB signaling .